Corruption and default risk: global evidence - Nadarajah, Sivathaasan; Atif, Muhammad; Tawiah, Vincent; Liu, Jia; Wood, Geoffrey (Wiley, 2025)
The extant literature explores the consequences of corruption on firms’ growth and survival. However, its impact on default risk remains unexplored. On the basis of a sample of 189,109 firm‐years from 2004 to 2021 across 47 countries, our study reveals that a one standard deviation increase in corruption is associated with an 11.3% increase in default risk. Our channel analysis identifies information asymmetry and managerial risk‐taking as key mechanisms through which corruption influences default risk. This adverse effect is particularly pronounced in countries with opaque information environments, weak governance frameworks and inadequate external monitoring of firms. We further highlight the detrimental impact of corruption on firms’ borrowing costs and banks’ loan performance. Our study emphasizes the importance of enhancing information transparency and implementing stringent control mechanisms as a basis of mitigating corruption's detrimental effects across a range of different socio‐political contexts.
Keywords: 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; 16 Peace, Justice and Strong Institutions; Finance; 3501 Accounting, auditing and accountability; 3502 Banking, finance and investment; corruption; default risk; external monitoring; governance frameworks; information asymmetry; risk-taking